Metastatic pulmonary synovial sarcoma: A double coincidence: Case report - Khadija Laasri, MD; Meriem Zhim, MD; Ismail Mohamed Halfi, MD; Kaoutar Imrani, MD; Nabil Moatassim Billah, PhD; Ittimade Nassar, PhD (Radiology Case Reports, 2023)
Synovial sarcomas are considered as one of the most aggressive neoplasms that account for approximately 8% of all soft tissue sarcomas; they are mainly localized in soft tissues of the extremities and joints and rarely occur in the thorax. In this case report, we describe a 34-year-old woman presenting a chest pain with a chest radiography showing a mass lesion occupying two-thirds of the right hemi-thorax. A malignant pulmonary tumor was suspected after CT imaging revealing a bilateral renal metastasis, and then a spindle-cell carcinoma was thought-about. The post-operative pathological analysis of the main mass confirmed the diagnosis of a pulmonary synovial sarcoma.